A Comparison on Emotional Intelligence and Responsibility of the Female Intelligent versus Ordinary High School Students - Moradi, Ensieh (Journal of Entrepreneurship, Business and Economics, 2016)
The main aim of the present study is the analysis of the relationship between Emotional Intelligence and responsibility; thus, regarding the applied purpose and the data collection method, this study is a quantitative and non-experimental research; and in terms of conduction is descriptive of correlational type. The target population of this study comprises the entire female intelligent and ordinary students of Tehran who are enrolled at high school. The selected sample of this study is 220 students divided into 110 intelligent students and 110 ordinary students. The instrument of the study is the standard Daniel Goleman’s EI model questionnaires and Wright et al.’s (2008) PSQR standard questionnaire. The findings indicated that there is a meaningful discrepancy between intelligent and ordinary students’ EI and responsibility. Research paper Reference to this paper should be made as follows: Moradi, E. (2016). “A Comparison on Emotional Intelligence and Responsibility of the Female Intelligent versus Ordinary High School Students”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 148–163.